Factors attracting the use of public private partnership in Malaysia - Ismail, Suhaiza (Universiti Sains Malaysia Press, 2013)
The study aims to investigate the factors that attract the adoption of public private partnership (PPP) in Malaysia. It also intends to examine the differences in the perception of those factors by the government and private sector. A questionnaire survey was used to elicit the perceptions of the public and private sectors on the attractive factors of PPP adoption in Malaysia. One hundred and twenty two usable responses were analysed using Statistical Package for the Social Science (SPSS) to rank the importance of the factors based on the overall responses, as well as the responses from both the public and the private sectors and to examine the differences in the perceptions between the two sectors. The overall results show that "facilitate creative and innovative approaches", "solve the problem of public sector budget restraint", "provide an integrated solution", "benefit local economic development" and "accelerate project development" are the top five attractive factors for adopting PPP in Malaysia. In terms of the differences in the perception between the public and private sector groups, the statistical test results indicated that there are significant differences in the perception for a number of factors. Keywords: Public private partnerships, Attractive factors, Malaysia